G394 Optimisation of vancomycin dosing regimen in newborns by performing a population pharmacokinetic analysis of prospectively collected data. (27th April 2016) - Gunaratnam, F; Germovsek, E; Basquet, F Bossacoma; Pereira, S; Standing, JF; Sinha, AK
Abstract : Background: Vancomycin is a commonly used antimicrobial to treat hospital acquired infections in neonates. Although both intermittent and continuous dosing regimens are used, there is limited data on population pharmacokinetics (PK) for continuous vancomycin usage to inform correct dosing. Aim: To determine the population PK parameters of vancomycin in neonatal patients with a wide range of gestational ages and birth weights receiving different dosing regimens. Methods: Data were collected prospectively from 56 newborns who were receiving vancomycin for late onset sepsis (32 on continuous infusion and 24 on intermittent dosage) following approval from Barts Health Clinical Effectiveness Unit. Peak and trough vancomycin concentrations were collected from infants on intermittent dosage, and random levels for continuous infusion. An enzymatic assay on the COBAS 702 platform was used to measure vancomycin (linear range 1.7–80 μg/ml). Population PK analysis was performed by simultaneously modelling both intermittent and continuous infusion data using nonlinear mixed-effects modelling (NONMEM 7.3). Results: There were 183 vancomycin samples available for analysis (n = 81 from the intermittent group, and n = 102 from infants on continuous infusion). The median (range) postnatal age at baseline was 26 (1–156) days; and gestational age 29 (23.7–41.9) weeks. The final model that provided the best fit to the data was a 1-compartment model. Allometric weight scaling and postmenstrual age (PMA) driven sigmoidal maturation function were included a priori and no further covariate provided a significant improvement in the model fit. The model was internally evaluated using basic diagnostic plots and a visual predictive check, which indicated that the model is able to describe the data and had good predictive power. The final parameter estimates (mean (relative standard error)) of clearance (CL) and volume of distribution (V) were 5.6 L/h/70 kg (5.3%) and 40.0 L/70 kg (9.3%), respectively. For a typical infant from the studied population (weight=1.7 kg, PMA=35.7 weeks), CL was 0.10 L/h, and V was 0.97 L. Conclusions: A population PK model was developed for both intermittent and continuous vancomycin dosage newborns and was shown to have good descriptive and predictive properties. This model will be used to develop a new dosing scheme which will then be prospectively evaluated.